Effect of Amla Juice on Growth Performance, Carcass Characteristics, and Lipid Profile of Broiler - Sah, Amar Kumar; Nurul, Amin, Md.; Salma, Ummay; Thakur, Mahesh; Thakur, Ayush Kumar (Nepalese Journal of Agricultural Sciences, 2025)
This study was carried out to evaluate the effect of Amla juice on growth performance, carcass characteristics, and lipid profile of broiler. This 35-day study at HSTU, Dinajpur, evaluated the effects of Amla juice in drinking water on broilers.120 chicks were divided into five groups (0%, 0.75%, 1%, 1.25%, and 1.5% Amla). The 1% group (T2) showed significantly higher body weight, better feed conversion ratio, and improved carcass traits. Lipid profiles improved with lower cholesterol and LDL, and higher HDL and triglycerides. T2 also yielded the highest net profit. Amla juice at 1% enhances growth, health, and profitability, making it a natural growth promoter in broiler production.